Continuous Cognitive Dynamics of the Evaluation of Trustworthiness in Williams Syndrome - Martens, Marilee A.; Hasinski, Adam E.; Andridge, Rebecca R.; Cunningham, William A. (Frontiers in Psychology, 2012)
The decision to approach or avoid an unfamiliar person is based in part on one’s evaluation of facial expressions. Individuals with Williams syndrome (WS) are characterized in part by an excessive desire to approach people, but they display deficits in identifying facial emotional expressions. Likert-scale ratings are generally used to examine approachability ratings in WS, but these measures only capture an individual’s final approach/avoid decision. The present study expands on previous research by utilizing mouse-tracking methodology to visually display the nature of approachability decisions via the motor movement of a computer mouse. We recorded mouse movement trajectories while participants chose to approach or avoid computer-generated faces that varied in terms of trustworthiness. We recruited 30 individuals with WS and 30 chronological age-matched controls (mean age = 20 years). Each participant performed 80 trials (20 trials each of four face types: mildly and extremely trustworthy; mildly and extremely untrustworthy). We found that individuals with WS were significantly more likely than controls to choose to approach untrustworthy faces. In addition, the maximum deviation analysis demonstrated that even when ultimately choosing to avoid an untrustworthy face, the individuals with WS were more “tempted” than controls to deviate toward ‘Approach’ before deciding to ‘Avoid’ the face. We also found that the individuals with WS were more likely to choose to avoid trustworthy faces than controls, which might be associated with the neutral facial expressions displayed by the trustworthy faces. Both the WS and control participants were able to discriminate between mild and extreme degrees of trustworthiness and were more likely to make correct approachability decisions as they grew older. These findings increase our understanding of the cognitive processing that underlies approachability decisions in individuals with WS.